Resistensi Kritis Ki Hadjar Dewantara pada Surat Kabar De Express: Sebuah Kajian Postkolonialisme - Masjid, Akbar Al; Trisharsiwi, Trisharsiwi; Setiawan, Arya Dani; Marwanti, Endah (GERAM: Gerakan Aktif Menulis, 2023)
Postcolonialism literary criticism is a critical approach to literature that involves the historical context of colonialism and its impact on culture, identity, and power. Postcolonial literary criticism also helps provide an understanding of the concept of 'the Other', i.e., the way in which colonial culture denigrates and belittles other cultures outside its nation. This study aims to examine the article by Ki Hadjar Dewantara written in the newspaper Express with an approach to literary criticism of postcolonialism. This type of research is a descriptive qualitative literature study with an analysis method, namely content analysis. The source of this research data is an article entitled "Als ik een Nederlander was" or "If I Were a Dutchman," written by Ki Hadjar Dewantara (KHD) and published in De Express Newspaper on July 13, 1913. The research data is in the form of discourse quotes contained in the article. Data collection techniques include read, listen, and record techniques. The findings contained resistance in the form of mimicry, hybridity, and ambivalence. The resistance to mimicry or imitation shown by KHD is included in the category of closed or covert reciprocity because the rejection of the policies implemented by the Dutch government is opposed by writing that contains subtle but sharp satire. Hibridity resistance is found in the choice of KHD diction that deliberately explores and contrasts the words inlander-nederlander, freedom and slavery, freedom and oppression. The ambivalence resistance that was found was KHD, who initially wanted to become a Dutchman with his various arguments that flattered as well as satirized and gave condemnation to the colonial nation as KHD's strategy in awakening the patriotism and nationalism of the Indonesian people to fight for independence.